Behind Buffett’s curtain: Love and passion amongst senior executives - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2011)
Much has been written about the legendary investment skills of Warren Buffett and the business empire he has built. However, much lesser known are the executives who are the day-to-day managers of the various portfolio companies under Berkshire Hathaway. In his book, Behind the Berkshire Hathaway Curtain, first-time author Ronald Chan offers a refreshing insight into the lives and ideals of a group of Buffett’s lieutenants.